Reproductive Health, Economic Growth and Poverty Reduction in Africa : Frameworks of Analysis - Mwabu, Germano M.; Ajakaiye, David Olusanya Ishola (Book collections on Project MUSE., 2010)
This volume contains framework papers prepared for a collaborative research project on Reproductive Health, Economic Growth and Poverty Reduction in Africa, an initiative of the African Economic Research Consortium (AERC). Taken together, the chapters in this book make a compelling argument that improvement in reproductive health is key to raising household incomes and to reducing poverty. the books reveals that the triple phenomena of better reproductive health, economic growth, and declining poverty, are likely to be found in an environment in which labour and product markets function. Further, a macroeconomic framework that encourages domestic and foreign investments and promotes social protection for current and future generations is essential.